Dynamics of TNF-α and INF-γ content in blood serum in connection with the marker profile of patients with acute hepatitis B at different degrees of severity of the disease - A. B. Khelemendyk (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The aim – is to analyze the dynamics of the content of TNF-α and INF-γ in the serum in connection with the marker profile of patients with acute hepatitis B at different degrees of severity of the disease.